2016
DOI: 10.1159/000452222
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Distigmine on Electrical Field Stimulation-Induced Contraction of Mouse Urinary Bladder Smooth Muscles

Abstract: Distigmine bromide (distigmine), a reversible carbamate cholinesterase inhibitor, is used in Japan for treating detrusor underactivity, myasthenia gravis, and glaucoma. Although there is clinical evidence about the effectiveness of distigmine in the treatment of detrusor underactivity, mechanisms by which distigmine restores impaired urinary bladder smooth muscle (UBSM) contractility have not been fully investigated. The aims of this study were to investigate the potentiating effects of distigmine on UBSM cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…However, looking at the urodynamic reports in MG (Table 3 ) and neuro-urology reports [ 8 , 9 ], there might be a direct cause and/or a secondary or associated cause producing LUTS in MG. Detrusor overactivity (DO; as seen in Table 1 ) is usually attributed to the brain/supra-sacral spinal cord lesions, but it might also originate from partial peripheral nerve lesion (by irritation and ephaptic transmission of the nerve fibers). Another possibility for DO is that pyridostigmine, commonly prescribed to ameliorate muscular weakness in MG, stimulates bladder smooth muscles enough to generate DO [ 12 ]. In our previous study [ 13 ], a 42-year-old man with MG (MGFA2, under 120 mg/day pyridostigmine) showed DO and small bladder capacity (150 mL) on urodynamics.…”
Section: Discussionmentioning
confidence: 99%
“…However, looking at the urodynamic reports in MG (Table 3 ) and neuro-urology reports [ 8 , 9 ], there might be a direct cause and/or a secondary or associated cause producing LUTS in MG. Detrusor overactivity (DO; as seen in Table 1 ) is usually attributed to the brain/supra-sacral spinal cord lesions, but it might also originate from partial peripheral nerve lesion (by irritation and ephaptic transmission of the nerve fibers). Another possibility for DO is that pyridostigmine, commonly prescribed to ameliorate muscular weakness in MG, stimulates bladder smooth muscles enough to generate DO [ 12 ]. In our previous study [ 13 ], a 42-year-old man with MG (MGFA2, under 120 mg/day pyridostigmine) showed DO and small bladder capacity (150 mL) on urodynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these contractions were caused by both ACh (the atropine-sensitive component) and ATP (the α,β-mATP-sensitive component). 44) To confirm that distigmine augments the ACh-induced contractile component, we examined its effects on contraction generated in the presence of α,β-mATP (10 −4 M). Distigmine (10 −6 M) substantially enhanced the contractile component and subsequent atropine (10 −6 M) administration almost completely suppressed it (Fig.…”
Section: Effects Of Distigmine On Ubsm Contrac-tile Responses Elicitementioning
confidence: 99%
“…Therefore, distigmine clearly augmented the ACh-mediated contractile component. 44) We also examined the effects of distigmine on the EFSinduced contractile component generated in the presence of atropine to verify that distigmine does not influence ATPinduced contraction. Distigmine (10 −6 M) did not significantly affect the contractile component generated in the presence of atropine (10 −6 M) (p >0.05 for atropine (10 −6 M) vs. atropine (10 −6 M) + distigmine (10 −6 M)).…”
Section: Effects Of Distigmine On Ubsm Contrac-tile Responses Elicitementioning
confidence: 99%
“…Therefore, our laboratory started pharmacological studies on the effects of distigmine on urinary bladder (UB) motility and has previously reported results supporting the clinical effectiveness and usefulness of distigmine. [10][11][12][13][14][15][16][17][18] The most remarkable pharmacological characteristic of distigmine was the persistence of its effect. In particular, distigmine was found to potentiate the UB internal pressure via the micturition reflex for more than 12 h. 17) Interestingly, the long-lasting potentiating effect of distigmine on intravesical pressure persisted even after distigmine disappeared from the blood.…”
mentioning
confidence: 99%